Implementation of Cyber Public Relations in Managing Digital Communication at Museum Sandi Yogyakarta - Dias Regian Pinkan; Hari Akbar Sugiantoro (Jogjakarta Communication Conference (JCC), 2026)
The development of digital media has significantly transformed how organizations communicate with their publics, including cultural institutions such as museums. This study aims to examine the implementation of Cyber Public Relations in managing digital communication at Museum Sandi. This research employs a qualitative descriptive method. Data were collected through in-depth interviews, observation of digital communication activities, and documentation of the museum’s digital platforms. The primary informant in this study was Setyo Budi Prabowo. The analysis focuses on the strategies used in digital communication, content production and management, audience interaction, as well as challenges faced in implementing Cyber PR. The results show that Museum Sandi actively utilizes digital platforms, particularly Instagram and TikTok, to disseminate educational information about cryptography history and museum activities. The museum also implements thematic content such as “Selasa Sejarah” and “Kamis Syber” to maintain consistency in communication. Digital communication activities are managed by a small internal team responsible for content creation and interaction with audiences. The use of social media has contributed to increasing public awareness and attracting visitors, as many visitors report learning about the museum through digital platforms. However, challenges remain, including limited human resources and uneven internal understanding of digital communication practices.